2022
DOI: 10.3390/molecules27041170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cationic Lipid Nanoparticle Loaded siRNA with Stearylamine against Chikungunya Virus

Abstract: Chikungunya is an infectious disease caused by mosquito-transmitted chikungunya virus (CHIKV). It was reported that NS1 and E2 siRNAs administration demonstrated CHIKV inhibition in in vitro as well as in vivo systems. Cationic lipids are promising for designing safe non-viral vectors and are beneficial in treating chikungunya. In this study, nanodelivery systems (hybrid polymeric/solid lipid nanoparticles) using cationic lipids (stearylamine, C9 lipid, and dioctadecylamine) and polymers (branched PEI-g-PEG -P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In recent years, cationic lipid-based siRNA therapy had an excellent contribution to the treatment of several diseases [ 6 ]. There are several reports on the use of cationic lipid-based gene delivery for treating diseases [ 7 9 ]. There are different viral and nonviral delivery vectors available.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cationic lipid-based siRNA therapy had an excellent contribution to the treatment of several diseases [ 6 ]. There are several reports on the use of cationic lipid-based gene delivery for treating diseases [ 7 9 ]. There are different viral and nonviral delivery vectors available.…”
Section: Introductionmentioning
confidence: 99%
“…It might be due to the concentration of Lipofectamine 2000 used to transfect the siRNA might not be enough to serve as an effective carrier as a result of which, adequate levels of siRNA could not be delivered to the cells to initiate RNAi. Due to the restrictions of cytotoxicity (∼15–20%) in Vero CCL-81 cells, the concentration of Lipofectamine 2000 used could not be increased any further ( Jeengar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…siRNA targeted against E2 and nsP1 genes (designated as Chik1 and Chik5, respectively) were designed using HP OnGuard siRNA design and synthesized (Qiagen, Germany) as described previously ( Parashar et al, 2013 ). The minimum effective dose of siRNA as was investigated earlier to be 400 pM ( Jeengar et al, 2022 ), was used during the synthesis of siRNA encapsulated ZIF-C nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…It distributes asymmetrically in the lipid bilayer, located mainly on the outer surface of the liposomes [41]. Studies on SA-nanoparticles showed increased stability, minimised drug leakage, and a controlled release profile [42]. However, cytotoxicity limits the clinical use of SA as the hydrophilic nitrogen 'head' group of the molecule interacts with certain enzymes [36,42].…”
Section: Modification Of Zeta Potentialmentioning
confidence: 99%
“…Studies on SA-nanoparticles showed increased stability, minimised drug leakage, and a controlled release profile [42]. However, cytotoxicity limits the clinical use of SA as the hydrophilic nitrogen 'head' group of the molecule interacts with certain enzymes [36,42]. Other works reported apoptosis induced by SA generating reactive oxygen species, activating protein kinase C, or enhancing the release of apoptosis-dependent proteins, and hemolysis arising from the interaction between the molecule and the negatively charged erythrocyte membrane [43,44].…”
Section: Modification Of Zeta Potentialmentioning
confidence: 99%